Epistemic game of moderate physics-capable students’ by SOLO taxonomy in completing fluid mechanics problems - M D M Puspitasari; K Nadliroh; M N Muzaki (International Conference on Mathematics and Science Education of Universitas Pendidikan Indonesia, 2021)
The students’ thinking process in completing problems is able to show epistemic game. SOLO taxonomy is used to categorize the students’ thinking process. The researcher to collect data use test and interview. The test is consisted of fluid mechanics test and physics understanding test. Physics understanding test is used to determine the level of students’ physics understanding, while the fluid mechanics test is used to determine students’ epistemic game by SOLO taxonomy to solve the problems. The analysis result of the first test showed that the game used to solve problems was mapping mathematics to meaning in relational level and transliteration to mathematics in multistructural level. In the second test, the students used pictorial analysis in extended abstract level and transliteration to mathematics level in relational in solving problems. Meanwhile, the students used mapping mathematics to meaning in relational level, and recursive plug and chug in relational level to solve the problems in the third test. Furthermore, the fourth test was completed by recursive plug and chug in relational level. Epistemic game by SOLO taxonomy of this research can be used to determine learning strategy or model which is compatible with learning material concepts.